Rethinking modularity; designing a prototype for checkered stacking - Müller Zitzke, Paul (My University, 2024)
Modular prefabrication offers a number of advantages in comparison to conventional construction, including reduced construction time, minimised material waste, reduced labour costs and improved quality control. However, modular construction faces challenges in relation to logistical, spatial and structural issues. Through the development of a modular prototype, this research aims to contribute an innovative modular con‐ struction solution, particularly an alternative method of stacking the modules, in order to address these issues. The prototype draws inspiration from the project Sneglehusene by BIG, which includes the stacking of modules in a checkered pattern. This idea serves as a starting point for the prototype, while developing its concept further.
Keywords: Prefabrication, Modular Prototype, Checkered Stacking